Making Gamification Easy for the Professor: Decoupling Game and Content with the StudyNow Mobile App - Feldotto, Matthias; John, Thomas; Kundisch, Dennis; Hemsen, Paul; Klingsieck, Katrin; Skopalik, Alexander (Proceedings of the 12th International Conference on Design Science Research in Information Systems and Technology (DESRIST))
Many university students struggle with motivational problems, and gamification has the potential to address these problems. However, gamification is hardly used in education, because current approaches to gamification require instructors to engage in the time-consuming preparation of their course contents for use in quizzes, mini-games and the like. Drawing on research on limited attention and present bias, we propose a "lean" approach to gamification, which relies on gamifying learning activities (rather than learning contents) and increasing their salience. In this paper, we present the app StudyNow that implements such a lean gamification approach. With this app, we aim to enable more students and instructors to benefit from the advantages of gamification.

Towards a Lean Approach for Gamifying Education - John, Thomas; Feldotto, Matthias; Hemsen, Paul; Klingsieck, Katrin; Kundisch, Dennis; Langendorf, Mike (Proceedings of the 25th European Conference on Information Systems (ECIS))
Many university students struggle with motivational problems, and gamification has the potential to address these problems. However, using gamification currently is rather tedious and time-consuming for instructors because current approaches to gamification require instructors to engage in the time-consuming preparation of course contents (e.g., for quizzes or mini-games). In reply to this issue, we propose a “lean” approach to gamification, which relies on gamifying learning activities rather than learning contents. The learning activities that are gamified in the lean approach can typically be drawn from existing course syllabi (e.g., attend certain lectures, hand in assignments, read book chapters and articles). Hence, compared to existing approaches, lean gamification substantially lowers the time requirements posed on instructors for gamifying a given course. Drawing on research on limited attention and the present bias, we provide the theoretical foundation for the lean gamification approach. In addition, we present a mobile application that implements lean gamification and outline a mixed-methods study that is currently under way for evaluating whether lean gamification does indeed have the potential to increase students’ motivation. We thereby hope to allow more students and instructors to benefit from the advantages of gamification.

Continuous Speed Scaling with Variability: A Simple and Direct Approach - Antoniadis, Antonios; Kling, Peter; Ott, Sebastian; Riechers, Sören (Theoretical Computer Science)
We consider an extension of the dynamic speed scaling scheduling model introduced by Yao et al.: A set of jobs, each with a release time, deadline, and workload, has to be scheduled on a single, speed-scalable processor. Both the maximum allowed speed of the processor and the energy costs may vary continuously over time. The objective is to find a feasible schedule that minimizes the total energy costs. Theoretical algorithm design for speed scaling problems often tends to discretize problems, as our tools in the discrete realm are often better developed or understood. Using the above speed scaling variant with variable, continuous maximal processor speeds and energy prices as an example, we demonstrate that a more direct approach via tools from variational calculus can not only lead to a very concise and elegant formulation and analysis, but also avoids the “explosion of variables/constraints” that often comes with discretizing. Using well-known tools from calculus of variations, we derive combinatorial optimality characteristics for our continuous problem and provide a quite concise and simple correctness proof.

Automatic Derivation of Geometric Properties of Components From 3D Polygon Models - Brandt, Sascha; Fischer, Matthias; Gerges, Maria; Jähn, Claudius; Berssenbrügge, Jan (Volume 1: 37th Computers and Information in Engineering Conference)
To detect errors or find potential for improvement during the CAD-supported development of a complex technical system like modern industrial machines, the system’s virtual prototype can be examined in virtual reality (VR) in the context of virtual design reviews. Besides exploring the static shape of the examined system, observing the machines’ mechanics (e.g., motor-driven mechanisms) and transport routes for the material transport (e.g., via conveyor belts or chains, or rail-based transport systems) can play an equally important role in such a review. In practice it is often the case, that the relevant information about transport routes, or kinematic properties is either not consequently modeled in the CAD data or is lost during conversion processes. To significantly reduce the manual effort and costs for creating animations of the machines complex behavior with such limited input data for a design review, we present a set of algorithms to automatically determine geometrical properties of machine parts based only on their triangulated surfaces. The algorithms allow to detect the course of transport systems, the orientation of objects in 3d space, rotation axes of cylindrical objects and holes, the number of tooth of gears, as well as the tooth spacing of toothed racks. We implemented the algorithms in the VR system PADrend and applied them to animate virtual prototypes of real machines.

Automatische Ableitung der Transportwege von Transportsystemen aus dem 3D-Polygonmodell - Brandt, Sascha; Fischer, Matthias (Wissenschaftsforum Intelligente Technische Systeme (WInTeSys) 2017)
In der CAD-unterstützten Entwicklung von technischen Systemen (Maschinen, Anlagen etc.) werden virtuelle Prototypen im Rahmen eines virtuellen Design-Reviews mit Hilfe eines VR-Systems gesamtheitlich betrachtet, um frühzeitig Fehler und Verbesserungsbedarf zu erkennen. Ein wichtiger Untersuchungsgegenstand ist dabei die Analyse von Transportwegen für den Materialtransport mittels Fließbändern, Förderketten oder schienenbasierten Transportsystemen. Diese Transportwege werden im VR-System animiert. Problematisch dabei ist, dass derartige Transportsysteme im zugrundeliegenden CAD-Modell in der Praxis oft nicht modelliert und nur exemplarisch angedeutet werden, da diese für die Konstruktion nicht relevant sind (z.B. der Fördergurt eines Förderbandes, oder die Kette einer Förderkette), oder die Informationen über den Verlauf bei der Konvertierung der Daten in das VR-System verloren gehen. Bei der Animation dieser Transportsysteme in einem VR-System muss der Transportweg also aufwändig, manuell nachgearbeitet werden. Das Ziel dieser Arbeit ist die Reduzierung des notwendigen manuellen Nachbearbeitungsaufwandes für das Design-Review durch eine automatische Berechnung der Animationspfade entlang eines Transportsystems. Es wird ein Algorithmus vorgestellt, der es ermöglicht mit nur geringem zeitlichem Benutzeraufwand den Animationspfad aus den reinen polygonalen dreidimensionalen Daten eines Transportsystems automatisch zu rekonstruieren.

Gathering Anonymous, Oblivious Robots on a Grid - Fischer, Matthias; Jung, Daniel; Meyer auf der Heide, Friedhelm (Algorithms for Sensor Systems - 13th International Symposium on Algorithms and Experiments for Wireless Sensor Networks, ALGOSENSORS)

A Communication-Efficient Distributed Data Structure for Top-k and k-Select Queries - Biermeier, Felix; Feldkord, Björn; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Proceedings of the 15th Workshop on Approximation and Online Algorithms (WAOA))

A Continuous Strategy for Collisionless Gathering - Podlipyan, Pavel; Li, Shouwei; Markarian, Christine; Meyer auf der Heide, Friedhelm (Proceedings of the 13th International Symposium on Algorithms and Experiments for Wireless Networks (ALGOSENSORS))

An Evolutionary Robotics Approach to the Control of Plant Growth and Motion: Modeling Plants and Crossing the Reality Gap - Wahby, Mostafa; Hofstadler, Daniel Nicolas; Heinrich, Mary Katherine; Zahadat, Payam; Hamann, Heiko (Proc. of the 10th International Conference on Self-Adaptive and Self-Organizing Systems)
The self-organizing bio-hybrid collaboration ofrobots and natural plants allows for a variety of interestingapplications. As an example we investigate how robots can beused to control the growth and motion of a natural plant, using LEDs to provide stimuli. We follow an evolutionaryrobotics approach where task performance is determined bymonitoring the plant's reaction. First, we do initial plantexperiments with simple, predetermined controllers. Then weuse image sampling data as a model of the dynamics ofthe plant tip xy position. Second, we use this approach toevolve robot controllers in simulation. The task is to makethe plant approach three predetermined, distinct points in anxy-plane. Finally, we test the evolved controllers in real plantexperiments and find that we cross the reality gap successfully. We shortly describe how we have extended from plant tipto many points on the plant, for a model of the plant stemdynamics. Future work will extend to two-axes image samplingfor a 3-d approach.

Self-Organized Construction with Continuous Building Material: Higher Flexibility Based on Braided Structures - Heinrich, Mary Katherine; Wahby, Mostafa; Divband Soorati, Mohammad; Hofstadler, Daniel Nicolas; Zahadat, Payam; Ayres, Phil; Stoy, Kasper; Hamann, Heiko (Proc. of the 1st International Workshop on Self-Organising Construction (SOCO))

Hybrid Societies: Challenges and Perspectives in the Design of Collective Behavior in Self-organizing Systems - Hamann, Heiko; Khaluf, Yara; Botev, Jean; Divband Soorati, Mohammad; Ferrante, Eliseo; Kosak, Oliver; Montanier, Jean-Marc; Mostaghim, Sanaz; Redpath, Richard; Timmis, Jon; Veenstra, Frank; Wahby, Mostafa; et al. (Frontiers in Robotics and AI)

Robot Self-Assembly as Adaptive Growth Process: Collective Selection of Seed Position and Self-Organizing Tree-Structures - Hamann, Heiko; Divband Soorati, Mohammad (IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS 2016))

Collective Decision with 100 Kilobots: Speed vs Accuracy in Binary Discrimination Problems - Dorigo, Marco; Hamann, Heiko; Valentini, Gabriele; Ferrante, Eliseo (Journal of Autonomous Agents and Multi-Agent Systems)

Existence and Properties of Pure Nash Equilibria in Budget Games - Drees, Maximilian

Population Coding: A New Design Paradigm for Embodied Distributed Systems - Hamann, Heiko; Valentini, Gabriele; Dorigo, Marco (10th Int. Conf. on Swarm Intelligence, ANTS 2016)

Robot Gardens: An Augmented Reality Prototype for Plant-Robot Biohybrid Systems - von Mammen, Sebastian; Hamann, Heiko; Heider, Michael (ACM Symposium on Virtual Reality Software and Technology (VRST))

Inspiration-Triggered Search: Towards Higher Complexities by Mimicking Creative Processes - Rybář, Milan; Hamann, Heiko (Proceedings of the Genetic and Evolutionary Computation Conference (GECCO 2016))

On the Definition of Self-organizing Systems: Relevance of Positive/Negative Feedback and Fluctuations - Khaluf, Yara; Hamann, Heiko (ANTS 2016)

Collective Perception of Environmental Features in a Robot Swarm - Valentini, Gabriele; Brambilla, Davide; Hamann, Heiko; Dorigo, Marco (10th Int. Conf. on Swarm Intelligence, ANTS 2016)

Congestion Games with Mixed Objectives - Leder, Lennart